Phylogenetic, species richness and logistic influences on the biodiscovery process in Cnidaria - Johnson, Mark P.; Baker, Bill J.; Conneely, Ellie-Ann; McKeever, Kate; Young, Ryan M.; Laguionie-Marchais, Claire; Allcock, A. Louise (Frontiers in Marine Science, 2022)
The extent to which any particular taxon supplies novel natural products depends on biological and evolutionary differences, and on decisions made by (or constraints on) biodiscovery scientists. The influences of different sources of variability on the biodiscovery process were examined in a study of the Cnidaria, a group recognised as an important source of novel marine natural products. The number of species with at least one novel metabolite within a genus was related to the number of species in the genus. This pattern implies that different genera do not differ in the probability of containing a species with novel natural products. Outlying points of this relationship were consistent with the ease of obtaining material through culturing organisms. The most productive five species were the sources of over 100 novel metabolites each. The distribution of novel metabolites across species showed no signs of exhausting novelty for the most productive source species. Novel metabolite drug likeness (ADMET-score) varied among genera. However, this pattern of variation was of the same degree as observed for molecular weights of metabolites, suggesting that differences among genera are generated by the decisions of analysts with different interests and do not reflect underlying biology. Biogeographic patterns of soft coral species with novel natural products were matched to regional species richness. Overall, the evidence for phylogenetic or spatial influences on the chance of finding novel metabolites was weak. The patterns are consistent with a constant chance of finding novel natural products across different species, with some constraints linked to ease of sampling or culturing and some reinforcement of biodiscovery in species that have previously been the source of novel metabolites.